Probing for optical and HI diffuse gas in MHONGOOSE galaxy UGCA 250 - de Villiers, Mikhail (Department of Astronomy, 2025)
Extraplanar diffuse ionised gas (eDIG) has been observed in external spiral galaxies as well as the Milky Way and is distinguished by its emission-line ratios and its rotational velocity lag with respect to the galactic disk. Similarly, there is a wealth of observational evidence for extraplanar gas in the form of neutral atomic hydrogen (HI) associated with spiral galaxies. The presence of extraplanar hydrogen emission around nearby galaxies is believed to be a direct consequence of active star formation processes in the galactic disk. MHONGOOSE is an HI Nearby Galaxies Legacy Survey of MeerKAT probing the neutral atomic hydrogen in and around local disk galaxies. UGCA 250 is an edge-on, late-type spiral (Sd) galaxy part of MHONGOOSE. This work searches for signatures of extraplanar gas associated with this galaxy through studying the kinematics of the HI using tilted-ring modelling and Gaussian decomposition. This is supplemented with high-resolution spectroscopic data from the Southern African Large Telescope (SALT) allowing for the detection of extraplanar gas in both its ionised and neutral states. We find interesting kinematics in both the optical and the radio, suggesting that the kinematics should be explained by more than a simple disk model adopted in this work. The end result is a multi-wavelength characterisation of the gas associated with this galaxy. Thus, we probe for multi-phase planar and extraplanar diffuse gas associated with this galaxy. This work illustrates how sensitive HI observations with MeerKAT can be combined with high-resolution spectroscopic SALT data to achieve a complete kinematic study of a nearby galaxy.